Effect of X-ray suppression system upon parameters of electrostatic accelerator ion beam - I. G. Ignat'ev; M. I. Zakharets; S. V. Kolinko; D. P. Shulha (Ядерна фізика та енергетика)
Experimental study results are presented for a beam profile and emittance of an electrostatic accelerator “Sokol” before and after being equipped with magnet X-ray suppression system.